Putting new economic geography to the test : free-ness of trade and agglomeration in the EU regions - Steven Brakman; Harry Garretsen; Marc Schramm (Center for Economic Studies and ifo Institute (CESifo), 2005)
Based on a new economic geography (NEG) model by Puga (1999), we use the equilibrium wage equation to estimate two key structural model parameters for the NUTS II EU regions. These estimations enable us to come up with an empirically grounded free-ness of trade parameter. In line with NEG theory, the estimation results show that a spatial wage structure exists for the EU regions. By going back to the theoretical model we then analyze the implications of the free-ness of trade parameter for the degree of agglomeration. Our main findings suggest that agglomeration forces still have only a limited spatial reach in the EU. Agglomeration forces appear to be rather localized. At the same time, confronting our empirical results with the underlying new economic geography model also brings out the limitations of empirical research in new economic geography.
Keywords: R12; J31; F12; 330; Neue ökonomische Geographie; Freihandel; Agglomerationseffekt; EU-Staaten